Prevalência, Virulência e sensibilidade às terapias antimicrobianas das cepas de enterecoccus faecalis e enterococcus faecium isoladas de infecções endodônticas - Santos, Ana Carolina Chipoletti dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Enterococcus faecium has become one of the most dreaded micro-organisms in nosocomial infections, due to its greater ease in acquiring resistance to antibiotics than E. faecalis. However, lack of studies focused on the isolation and identification of E. faecium in the oral cavity. The objectives of this study was to isolate and identify E. faecalis and E. faecium in root canals with endodontic infections and to compare strains of E. faecalis and E. faecium in sensitivity to conventional antibiotics and antimicrobial photodynamic therapy (PDT). Furthermore, these species were compared for virulence in vivo, using the model of experimental infection of Galleria mellonella. The strains of E. faecalis and E. faecium isolated from root canals were identified by the Rapid ID 32 Strep system and multiplex PCR. All isolates identified as E. faecalis and E. faecium were tested for antibiotic susceptibility E-test method for determination of minimal inhibitory concentration (MIC). Next, we selected some strains of E. faecalis and E. faecium sensitive and antibiotic-resistant clinical use in dentistry for in vitro susceptibility testing to antimicrobial photodynamic therapy. The virulence of strains of E. faecalis and E. faecium were tested in in vivo experimental model of infection of G. mellonella by analysis of larval survival curve and quantitation of CFU/mL bacterial cells present in the hemolymph of these animals. Data from CFU/mL obtained in photodynamic therapy and infection in G. mellonella were subjected to analysis of variance and Tukey test. The data on the survival of G. mellonella curves were analyzed by log-rank method. Samples of 38 root canals from different patients were performed and 22 had cultures positive for Enterococcus spp. (58%). Of these patients, all showed E. faecalis and only 2 had mixed infections with E. faecalis and E. faecium 6 isolates (27%) E. faecalis resistant to ....

Enterococcus faecium se tornou um dos mais temidos micro-organismos em infecções hospitalares, por apresentar maior facilidade em adquirir resistência aos antibióticos do que E. faecalis. Entretanto, faltam estudos voltados para o isolamento e identificação de E. faecium na cavidade bucal. Os objetivos deste trabalho foram isolar e identificar E. faecalis e E. faecium em canais radiculares com infecções endodônticas e comparar as cepas de E. faecalis e E. faecium em relação à sensibilidade aos antibióticos convencionais e à terapia fotodinâmica antimicrobiana (PDT). Além disso, essas espécies foram comparadas quanto à virulência in vivo, utilizando o modelo de infecção experimental de Galleria mellonella. As cepas de E. faecalis e E. faecium isoladas de canais radiculares foram identificadas pelo sistema Rapid ID 32 Strep e PCR multiplex. Todos os isolados identificados como E. faecalis e E. faecium, foram testadas quanto à sensibilidade aos antibióticos pelo método E-test para determinação da concentração inibitória mínima (MIC). A seguir, foram selecionadas algumas cepas de E. faecalis e E. faecium sensíveis e resistentes aos antibióticos de uso clínico na odontologia para testes de sensibilidade in vitro à terapia fotodinâmica antimicrobiana. A virulência das cepas de E. faecalis e E. faecium foram testadas in vivo no modelo de infecção experimental de G. mellonella por meio da análise da curva de sobrevivência das larvas e quantificação de UFC/mL de células bacterianas presentes na hemolinfa desses animais. Os dados de UFC/mL obtidos na terapia fotodinâmica e na infecção em G. mellonella foram submetidos à análise de variância e teste de Tukey. Os dados obtidos na curva de sobrevivência de G. mellonella foram analisados pelo método de Log-rank. Foram realizadas coletas de 38 canais radiculares de diferentes pacientes, sendo que 22 apresentaram culturas positivas para enterococcus spp.(58%)....
Keywords: Enterococcus faecalis; Fotoquimioterapia; Anti-infecciosos